Could homocysteine, angiotensin and alamandine be used as potential biomarkers in management of COVID-19? - Sahoo, Sibasish; T., Sasikala; V., Sampath Kumar; N., Lakshmanna (International Journal of Research in Medical Sciences, 2021)
The corona virus is now known as the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). Risk predictors and novel predictors associated with COVID-19 is required to enable the risk stratification, guide interventional studies to target patients at enhanced risk of developing severe disease risk and optimize the allocation of limited human and technical resources in the ongoing pandemic all over the globe. The present review focused on potential laboratory biomarkers associated with COVID-19. We carried out an electronic search in Medline (PubMed central), Scopus, Web of Science and using the keywords laboratory, biomarkers, novel biomarkers, corona virus 2019 or COVID-19. We observed that limited data were found that related to homocysteine and angiotensin II in COVID-19 patients. Hence original research on these novel biomarkers which associated with the complication of COVID-19 might be given new clues especially that mediate anti-inflammatory and anti-fibrotic effects leading to cardiovascular, renal-protective actions. The present review proposed by the available literature, these predictors might be the potent biomarkers to improve management of corona virus. Further, large cohort studies will be required to support conclusions of present review.